Agrochemical effects on plankton temporal variability are buffered at larger spatial scales - Barbosa, Gedimar Pereira [UNESP]; Vieira, Camila B. [UNESP]; dos Santos, Ana Carolina; Lara, Neliton [UNESP]; Mateus-Barros, Erick; Portinho, Jorge L. [UNESP]; Sarmento, Hugo; Perbiche-Neves, Gilmar [UNESP]; Veloso, Bianca; Montagner, Cassiana; Schiesari, Luis; Saito, Victor S.; et al. (Wiley, 2025)
Agricultural expansion affects ecosystem dynamics both locally and through regional‐scale processes. However, the way local and regional effects interact to influence temporal dynamics is not well understood. We conducted an outdoor freshwater mesocosm experiment to examine how localized agrochemical contamination, across different landscape compositions, influences the temporal variability of producers and consumers in planktonic food webs. We found that localized agrochemical contamination changed the temporal variability of local populations, but its effects varied across trophic levels. Insecticide contamination both increased the variability of consumers and reduced that of producer populations through cascading effects. Fertilizer contamination increased the variability of producer populations, but its effects on consumers were less pronounced. Temporal variability originating at the population level was buffered at higher levels of biological organization and spatial scales (communities and metacommunities). These results indicate that more complex systems, comprising interacting species and embedded in spatial dynamics, play an important role in reducing temporal variability, regardless of landscape composition and spatial heterogeneity. Our study reinforces the destabilizing effects of agrochemicals on freshwater planktonic food webs, and suggests that sustaining complex, spatially connected ecological systems could be crucial to biodiversity stability in highly modified agricultural landscapes.